MiR-219 regulates liver cancer stem cell expansion via E-cadherin pathway. Issue 24 (17th December 2019) - Si, Anfeng; Wang, Longqi; Miao, Kun; Zhang, Rongrong; Ji, Huiyu; Lei, Zhengqing; Cheng, Zhangjun; Fang, Xiangchun; Hao, Baobing
ABSTRACT: Liver cancer stem cells contribute to tumorigenesis, progression, recurrence and drug resistance of hepatocellular carcinoma (HCC). However, the underlying mechanism for the propagation of liverCSCs is not fully understood yet. Here we show that miR-219 is upregulated in liver CSCs. Knockdown of miR-219 attenuates the self-renewal and tumorigenicity of liver CSCs. Conversely, miR-219 overexpressing enhances the self-renewal and tumorigenicity of liver CSCs.Mechanistically, miR-219 downregulates E-cadherin via itsmRNA 3ʹUTR in liver CSCs. The correlation between miR-219 and E-cadherin is validated in human HCC tissues. Furthermore, the miR-219 expression determines the responses of hepatoma cells to sorafenib treatment. Our findings indicate that miR-219 plays a critical role in liver CSCs expansion and sorafenib response, rendering miR-219 as an optimal target for the prevention and intervention of HCC. Abbreviations: HCC: Hepatocellular carcinoma; CSCs: cancer stem cells; DMEM: Dulbecco's modified Eagle's medium; FBS: fetal bovine serum; OS: overall survival